Segment Reporting Disclosure under IFRS 8 and PSAK 108 in a Global and Indonesian Economic Uncertainty (2024–2025): Evidence from PT Tigaraksa Satria Tbk - Nanda Putra Saragi; Mustari (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study evaluates the compliance of segment reporting presented by PT Tigaraksa Satria Tbk with the requirements of IFRS 8 Operating Segments and PSAK 108 Segmen Operasi, considering the increasing global and Indonesian economic uncertainty that has heightened the need for transparent and reliable financial reporting. The study uses a qualitative descriptive approach based on secondary data obtained from the company's 2024 and 2025 annual reports and financial statements. The analysis applies the quantitative reportability criteria prescribed by IFRS 8 and PSAK 108, including the 10% revenue, profit or loss, and asset threshold tests, as well as the 75% external revenue requirement. The results show that only the Food and Household Needs segment satisfies all quantitative criteria as a reportable operating segment in both reporting periods. Meanwhile, the Gas (LPG) and Other Kitchen Appliances segment and the Books segment do not meet the required thresholds, although both continue to be disclosed in the financial statements. Overall, the company's segment reporting is consistent with the provisions of IFRS 8 and PSAK 108 and fulfills the required quantitative disclosure criteria. Nevertheless, the disclosures could be improved by providing clearer explanations regarding the inclusion of non-reportable segments, segment-specific risks, and the factors influencing changes in segment performance. Strengthening these qualitative disclosures would improve the transparency, comparability, and decision usefulness of financial information, particularly during periods of continued economic uncertainty.